Support in the development of the Green Growth Plan for Indonesia's Aceh Province - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
ICRAF supported the development of a plan to achieve the sustainable development goals through green economic growth from land-based renewable resources and support nationally determined contributions.